Modernism and hegemony : a materialist critique of aesthetic agencies - Larsen, Neil (Theory and history of literature ;, 1990)
A critique of high modernism from a newly formulated Marxist perspective, achieved through analyses of texts by Marx and Adorno, Manet's paintings, and the works of several Latin American writers. Annotation copyrighted by Book News, Inc., Portland, OR.